The current understanding of growing metallic filamentary crystals in an electric field - Артемьев, Сергей Робленович (Eastern-European Journal of Enterprise Technologies, 2015)
The existing ideas about one of the non-traditional methods of growing metallic filamentary crystals, such as growing in an electric field were considered in the paper. The role of impurities in the crystal growth process was investigated. Positive and negative sides of the electrolysis process during growing this group of crystals were critically considered. The experiments have shown that concentrated solutions of salts of several metals are the most suitable for growing filamentary crystals of metals and the presence of surface-active substances (SAS), having long molecules in the solution, is necessary for the nucleation of metallic filamentary crystals. The growth of metallic filamentary crystals is promoted by the presence of fine particles of graphite, glass and other mechanical impurities, and the presence of oxygen, on the contrary, retards it. During the formation of the whiskers of solder materials on thin-film electro-resistances when passing an electric current through them, whisker growth does not start immediately, but some time after the solder melts. The reason for the formation and growth of whiskers is the transferred-electron effect in a metal conductor, and the composition of the electrical resistance has no fundamental significance. The lack of oxygen in the electrolysis process is the basic condition for the formation of whiskers. Surface diffusion plays an important role in the formation of filamentary crystals. This research direction remains relevant at the present time. Today the country needs new structural materials that have valuable physicochemical properties. Microelectronics, medicine, defense issues, instrument-making industry, radiation safety, dosimetry, environmental protection - that's not all areas where grown filamentary crystals can be successfully used. Filamentary crystals have amazing properties, which in today's conditions deserve the close attention of our science. This, in turn, will help to more efficiently solve the issues of getting products that meet the requirements of environmental legislation, as well as human and environmental protection from anthropogenic factors.